Daily Activity Pattern of Geladas (Theropithecus gelada, Ruppell 1835) in Kotu Forest, Northern Ethiopia - Degu Abate; Zerihun Girma (The Scientific World Journal)
Gelada (Theropithecus gelada) is one of the endemic primates of Ethiopia. The ecology of meta populations of geladas outside protected areas is less studied, and their population status is uncertain. As a result, we conducted a study to investigate the daily activity pattern of gelada in Kotu forest and associated grasslands in northern Ethiopia from August 2017 to February 2018 covering both wet and dry seasons. The instantaneous scan sampling method was employed to collect behavioral data. The activity pattern of three selected focal groups of geladas was studied, and predominant behavioral activities were scanned in 15 minutes intervals from dawn 7:00 h to dusk at 18:00 h. Feeding comprised 61.65% of the total scan, followed by moving 18.49%. Feeding activity was more frequent during the dry season (about 65%) than in the wet season (58.20%). On the other hand, moving activity was more frequent during the dry season (about 22%) than in the wet season (about 14%). The daily activity pattern of gelada showed a feeding peak early in the morning and in the late afternoon. The time allocated by geladas for feeding and moving in the study area is higher than other activities. Therefore, there is a need for further in-depth research on diet availability and quality to justify why geladas allocate more time for feeding and moving nexus for conservation interventions.